Construct validation on organizational strategies and performance dimensions using confirmatory factor analysis - Abdullah, Haim Hilman; Kaliappen, Narentheren (Integrated Publishing Association, 2014)
The research tries to observe the psychometric properties of the organizational strategies and performance scales which consist of competitive strategy, market orientation, innovation strategy and organizational performance.SPSS v21 and Amos v20 were utilized to analyse the dataset.The outcomes found support for the fact that organizational strategies and performance can be measured by the four variables that adapted from prior literatures.The results also indicated adequate internal consistency and construct validity for all the variables.The findings show that instrumentation used in this study is a valuable and apt in evaluating the organizational strategies and performance in context of Malaysia hotel industry. Finally, implications, limitations and recommendations are also discussed.